Planning and reporting solution design for project management in SAP Analytics Cloud - Novotný, Jan; Pour, Jan; Borovec, Jakub; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This master thesis focuses on planning and reporting solution for project management. The aim of the thesis is to develop a self-service planning and reporting solution design by use of Runn software for planning part and SAP Analytics Cloud (SAC) platform for reporting part which project managers at NDC Group Czech s.r.o. will use for human resources utilization management. To achieve this goal is used an extensive specialized literature research together with qualitative research in the form of ongoing unstructured interviews. Firstly, the principles of cloud computing, cloud business intelligence and self-service business intelligence (SSBI) are analysed in relation to the thesis goal. Subsequently are analysed also the main project management principles and planning & reporting needs in the field of human resources utilization management to emphasize its importance for the company’s success. Next, the company NDC Group Czech s.r.o. is briefly analysed as well as the Runn software and SAC platform. Further, according to the project managers’ requirements is designed, implemented, and deployed first the planning solution in Runn and then the custom self-service reporting solution in SAC together with developed automated data model import jobs. The final solution allows project managers to effectively manage individual employee’s allocation on projects and prevent them from being either underutilized or overutilized.
Vedoucí práce: Jan Pour
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: řízení podnikové informatiky [obor dipl. práce]; diplomové práce; master's theses